2006
DOI: 10.15517/am.v11i1.17389
|View full text |Cite
|
Sign up to set email alerts
|

Selección de las líneas de maíz por resistencia a sequía.

Abstract: Drought is an important abiotic factor where maize is grown under rainfall conditions. In order to identify drought resistant lines, 77 S5 maize lines from the breeding program at Cotaxtla, Veracruz and four CML maize lines from CIMMYTwere evaluated under irrigation  (So) and drought stress (S1). Five indexes were applied to select drought tolerant lines. Four indexes use the grain yield as criteria for selection, these are, the drought index (DI), the arithmetic mean (AM), the geometric mean (GM), and the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…In general, this behavior is observed in most municipalities (Figure 5). Thus, the use of fertilizers, the adequate applications of agricultural practices, and the improvement in seeds generated a better corn yield in 2003-2018 [75][76][77][78][79][80][81][82].…”
Section: Dispersion Behavior Analysis Of the Anspir And Maximum Temperature In Each Study Variablementioning
confidence: 99%
See 1 more Smart Citation
“…In general, this behavior is observed in most municipalities (Figure 5). Thus, the use of fertilizers, the adequate applications of agricultural practices, and the improvement in seeds generated a better corn yield in 2003-2018 [75][76][77][78][79][80][81][82].…”
Section: Dispersion Behavior Analysis Of the Anspir And Maximum Temperature In Each Study Variablementioning
confidence: 99%
“…Investigations have demonstrated that the temperature increases can cause a yield reduction not only in corn, but also in beans, strawberry, and potato production, which have experienced crop reductions from 20% to 50% [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94]. For livestock, researchers found that growth, meat production, and milk (among others) are affected in warming environments [95].…”
Section: Dispersion Behavior Analysis Of the Anspir And Maximum Temperature In Each Study Variablementioning
confidence: 99%
“…El índice de tolerancia a sequía se ha utilizado como criterio para seleccionar genotipos por su tolerancia al estrés. Dicho índice consiste en comparar los tratamientos sometidos a estrés de una variable, sobre aquellos en condiciones normales de riego (Castañón et al, 2000;González et al, 2005). Con este índice, se pueden considerar los genotipos con los valores más altos como los más tolerantes; aquellos con los valores más bajos serán los más susceptibles.…”
Section: Introductionunclassified